Deciphering the performance of macrophages in tumour microenvironment: a call for precision immunotherapy - Belén Toledo; Linrui Zhu Chen; María Paniagua-Sancho; Juan Antonio Marchal; Macarena Perán; Elisa Giovannetti (Journal of Hematology & Oncology, 2024)
Abstract Macrophages infiltrating tumour tissues or residing in the microenvironment of solid tumours are known as tumour-associated macrophages (TAMs). These specialized immune cells play crucial roles in tumour growth, angiogenesis, immune regulation, metastasis, and chemoresistance. TAMs encompass various subpopulations, primarily classified into M1 and M2 subtypes based on their differentiation and activities. M1 macrophages, characterized by a pro-inflammatory phenotype, exert anti-tumoural effects, while M2 macrophages, with an anti-inflammatory phenotype, function as protumoural regulators. These highly versatile cells respond to stimuli from tumour cells and other constituents within the tumour microenvironment (TME), such as growth factors, cytokines, chemokines, and enzymes. These stimuli induce their polarization towards one phenotype or another, leading to complex interactions with TME components and influencing both pro-tumour and anti-tumour processes. This review comprehensively and deeply covers the literature on macrophages, their origin and function as well as the intricate interplay between macrophages and the TME, influencing the dual nature of TAMs in promoting both pro- and anti-tumour processes. Moreover, the review delves into the primary pathways implicated in macrophage polarization, examining the diverse stimuli that regulate this process. These stimuli play a crucial role in shaping the phenotype and functions of macrophages. In addition, the advantages and limitations of current macrophage based clinical interventions are reviewed, including enhancing TAM phagocytosis, inducing TAM exhaustion, inhibiting TAM recruitment, and polarizing TAMs towards an M1-like phenotype. In conclusion, while the treatment strategies targeting macrophages in precision medicine show promise, overcoming several obstacles is still necessary to achieve an accessible and efficient immunotherapy.